DICOM-SB at Imperial - Kitney,RI (2016)
This website hosts supporting information for the paper 'Towards the First Data Acquisition Standard in Synthetic Biology' (Sainz de Murieta, Bultelle, Kitney, 2016) .The paper describes the development of a new data acquisition standard for synthetic biology, called DICOM-SB, which is based on the highly successful Digital Imaging and Communications in Medicine (DICOM) standard in medicine. It also introduces a data model that has been specifically developed for synthetic biology. The model is a modular, extensible data model for the experimental process, which can optimize data storage for large amounts of data.